2019
DOI: 10.3390/f10100930
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungal Communities Are Influenced by Host Tree Species on the Loess Plateau, Northwest China

Abstract: Arbuscular mycorrhizal (AM) fungi can establish mutualistic symbioses with most terrestrial plants and therefore play a crucial role in the re-vegetation and rehabilitation of degraded ecosystems. Yet, little information is available on AM fungal communities associated with dominant tree species in the semi-arid region of the Loess Plateau, Northwest China. In this study, topsoil (0–20 cm) and subsoil (20–40 cm) samples were collected from the rhizosphere of five dominant tree species in northern Shaanxi Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Therefore, with such a small amount taken for testing in the sequencing of the ITS variable region for fungi in the NGS method, it could happen that this material has not been amplified. Similar results in AMF spores were obtained by authors of other papers [46][47][48]. Therefore, the results obtained by us are all the more valuable because both a modern research method (NGS in paper Grz ądziel and Gał ązka [11]) and traditional methods of counting AMF spores were used in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, with such a small amount taken for testing in the sequencing of the ITS variable region for fungi in the NGS method, it could happen that this material has not been amplified. Similar results in AMF spores were obtained by authors of other papers [46][47][48]. Therefore, the results obtained by us are all the more valuable because both a modern research method (NGS in paper Grz ądziel and Gał ązka [11]) and traditional methods of counting AMF spores were used in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…The European Parliament resolution (EP Resolution 2007) lists among the main threats to the proper functioning of soils a decrease in the content of OM, because its loss can cause many adverse phenomena associated with the disturbance of chemical, physical and biological processes that directly affect the quality of soil and its fertility [46][47][48][49][50]. Among the 8 types of analyzed soils, Gleyic Phaeozem, as a soil rich in organic matter, is the most sensitive to.…”
Section: Discussionmentioning
confidence: 99%
“…identified a total of 26 AMF species in the root zone of S. flavescens , which belong to 10 genera of AMF . The occurrence of AMF in the rhizosphere soils or within roots depends on the production of volatile substances by roots that attract AMF species, environmental factors, certain host preferences, physiological differences between the species, and cultural practices and vegetation in the locality. Also, many studies reported that AMF distribution is dependent on the influence of certain environmental factors such as organic carbon, total nitrogen, soil pH, moisture, and available nutrients in the soil…”
Section: Discussionmentioning
confidence: 99%
“…Many ecological conservation projects implemented in China restore the ecosystem and biodiversity based on scientific calculations and measurements. Many scholars have systematically evaluated them from the perspective of scientific knowledge [36,37]. However, in the early stages of this process, mainstream research believed that indigenous knowledge was unimportant, leading to a trend of marginalization of indigenous knowledge [38][39][40].…”
Section: Discussionmentioning
confidence: 99%